2013
DOI: 10.1007/s10329-013-0359-1
|View full text |Cite
|
Sign up to set email alerts
|

Feeding strategies of primates in temperate and alpine forests: comparison of Asian macaques and colobines

Abstract: We analyzed regional variation in the diets of two primate clades, Asian macaques and colobines, whose distributions include temperate-alpine forests. We addressed feeding strategies that enabled them to adapt to harsh environments characterized by relatively low mean temperatures and strong seasonality in both temperature and food availability. Macaques in tropical-lowland forests feed mainly on fruit and animal matter whereas populations in temperate-alpine forests feed more on foliage and on such items as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 80 publications
6
75
5
Order By: Relevance
“…This could be explained by the distribution of the edible mushrooms, the fact that only adult females have been seen to consume mushrooms and/or the placement of the camera traps (which are placed to focus on clouded leopards (Neofelis diardi) [Cheyne et al, 2013] Mushrooms provide little energy for most animals as they are difficult to digest [Claridge et al, 1999]. Yet foregut fermenters are able to extract more of the mushrooms' protein [Grueter et al, 2009;Tsuji et al, 2013], as is the case in marsupials [Claridge and Cork, 1994;McIlwee and Johnson, 1998] and it would be interesting to compare the diet of sympatric primates, e.g., orang-utans (Pongo pygmaeus), which are regularly seen to consume mushrooms in Sebangau and other sites [Galdikas, 1988;Harrison, 2009;Russon et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be explained by the distribution of the edible mushrooms, the fact that only adult females have been seen to consume mushrooms and/or the placement of the camera traps (which are placed to focus on clouded leopards (Neofelis diardi) [Cheyne et al, 2013] Mushrooms provide little energy for most animals as they are difficult to digest [Claridge et al, 1999]. Yet foregut fermenters are able to extract more of the mushrooms' protein [Grueter et al, 2009;Tsuji et al, 2013], as is the case in marsupials [Claridge and Cork, 1994;McIlwee and Johnson, 1998] and it would be interesting to compare the diet of sympatric primates, e.g., orang-utans (Pongo pygmaeus), which are regularly seen to consume mushrooms in Sebangau and other sites [Galdikas, 1988;Harrison, 2009;Russon et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…The subfamily Colobinae consists of predominantly leaf-eating primates [Chivers and Hladik, 1980;Oates et al, 1980;Kool, 1986;Duc et al, 2009;Matsuda et al, 2009] and has evolved gastro-intestinal adaptations to exploit this abundant resource [Bauchop and Martucci, 1968;Chivers, 1994]. A multi-chambered stomach containing a microbe suspension in the foregut, plus a capacious stomach chamber and elongated caecum simultaneously neutralize toxins and effectively break down plant wall cellulose, facilitating digestion of the high quantities of fibre, protein and vitamins generally contained within leaves and other less digestible foods [Bauchop and Martucci, 1968;Kay et al, 1976;Chivers, 1994;Kay and Davies, 1994;Tsuji et al, 2013].…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…For 3 decades after Ruhiyat [1983] had published the results of his fieldwork, his findings were often the only ones used for P. comata in comparative studies [e.g., van Schaik and Hörstermann, 1994;Bennett and Davies, 1994;Wright and Willis, 2012;Tsuji et al, 2013]. Other studies that were published on P. comata in mainstream scientific journals over this period that contained primary data dealt with distribution, conservation, or taxonomy [Weitzel and Groves, 1985;Melish and Dirgayusa, 1996;Nijman, 1997a, b;Nijman and van Balen, 1998;Meyer et al, 2011;Supartono et al, 2016]; the few ecological studies that were conducted either appeared in Indonesian journals, internal reports or remained hidden in unpublished theses [Sujatnika, 1992;Wedana, 1993;Nurdiana, 1997;Sugarjito et al, 1997;Nurjaman et al, 2002;Heriyanto and Iskandar, 2004;Suryana, 2010;Sawitri et al, 2010;Syarifah, 2013;Hidayat, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on non-human primates have shown that they may respond to a reduction in food availability by incorporating scarce but high-return foods or by optimizing their food intake on abundant but low-quality food [Hill et al, 2003;Sayers & Norconk, 2008;Tsuji et al, 2013;van Doorn et al, 2010;Wrangham et al, 1998]. The strategy they adopt may lead them to a diet including low profitability (e.g., energy/handling time) items (like Himalayan gray langurs, Semnopithecus entellus, in winter [Sayers et al, 2010] Most species of primates exhibit some degree of diet flexibility that allows them to cope with seasonality of resource availability or with intersite differences of habitat quality due to altitude, latitude, habitat fragmentation/loss, or habitat degradation [Campbell-Smith et al, 2011;Chaves & Bicca-Marques, 2013;Chaves et al, 2012;NaughtonTreves et al, 1998;Quéméré et al, 2013;Riley, 2007;Singh et al, 2001;Tsuji et al, 2013;Xiang et al, 2007]. Even species broadly and stereotypically described as dietary specialists are able to modify their dietary composition in response to habitat change (folivores such as colobines, [Grueter et al, 2009b;Koenig & Borries, 2001;Sayers & Norconk, 2008;Sayers et al, 2010;Xiang et al, 2007], or frugivores [Russo et al, 2005;Wieczkowski & Kinnaird, 2008]).…”
Section: Introductionmentioning
confidence: 99%